2022
DOI: 10.1021/acs.chemmater.2c00326
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Rare Earth-Containing Double Phosphates of the Type A3Ln(PO4)2 (Ln = Y, La, Pr, Nd, and Sm–Lu) as Potential Nuclear Waste Forms

Abstract: A new series of rubidium rare earth double phosphates is presented. High-quality single crystals of Rb 3 Ln-(PO 4 ) 2 (Ln = Y, La, Pr, Nd, and Sm−Lu) were grown via hightemperature flux growth methods. The Rb 3 Ln(PO 4 ) 2 (Ln = La, Pr, Nd, and Sm−Tb) phases crystallize in space group P2 1 /m, and the Rb 3 Ln(PO 4 ) 2 (Ln = Y and Dy−Lu) phases crystallize in space group P31m. A thermally induced and reversible structural transition, due to a change in the denticity of a rare earth-ligated phosphate group, is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Complete amorphization at 0.041 dpa indicates a low resistance to radiation damage for the Na x MAn 6 F 30 structure type. For comparison, radiation damage studies on potential waste form structures reported previously by others in the CHWM research group include a double phosphate Rb 3 Nd-(PO 4 ) 2 with single crystal amorphization dose at 0.22 dpa, a nanocrystalline phase at 0.52 dpa, 30 and a hollandite crystal Cs 1.33 Zn 0.67 Ti 7.33 O 16 at 0.538 dpa. 31 Other radiation damage studies found in the literature reported by other groups include the pyrochlore Ca 1.25 U 0.76 Zr 0.2 Ti 1.89 O 7 with an amorphization dose of 0.24 dpa 32 and a brannerite structure UTi 2 O 6 at 0.15 dpa.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete amorphization at 0.041 dpa indicates a low resistance to radiation damage for the Na x MAn 6 F 30 structure type. For comparison, radiation damage studies on potential waste form structures reported previously by others in the CHWM research group include a double phosphate Rb 3 Nd-(PO 4 ) 2 with single crystal amorphization dose at 0.22 dpa, a nanocrystalline phase at 0.52 dpa, 30 and a hollandite crystal Cs 1.33 Zn 0.67 Ti 7.33 O 16 at 0.538 dpa. 31 Other radiation damage studies found in the literature reported by other groups include the pyrochlore Ca 1.25 U 0.76 Zr 0.2 Ti 1.89 O 7 with an amorphization dose of 0.24 dpa 32 and a brannerite structure UTi 2 O 6 at 0.15 dpa.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…30 series since compounds containing these two cations were successfully synthesized for all five elements, Ce, Th, U, Np, and Pu. The data and graphs can be seen in Table2and Figure3below.…”
mentioning
confidence: 99%
“…38,39 The high radiation damage tolerance of Rb 3 Ln(PO 4 ) 2 (Ln = Y, La, Pr, Nd, and Sm–Lu) provides the possibility as potential nuclear waste form materials. 40 To date, a great number of rubidium-based phosphates have been discovered and reported, such as RbNiFe(PO 4 ) 2 , 41 RbZn(PO 3 ) 3 42 and Rb 6 Bi 4 (PO 4 ) 2 (P 2 O 7 ) 3 . 43…”
Section: Introductionmentioning
confidence: 99%
“…To investigate materials that have potential as future nuclear waste forms, we have focused on crystalline materials, including oxides, fluorides, phosphates, and, as described herein, borates. The investigation of TRU elements is difficult due to their high level of radioactivity, prompting the use of surrogates such as Nd 3+ and Eu 3+ for Am 3+ and Cm 3+ in exploratory chemistry since their oxidation states, ionic radii, and coordination preferences are virtually identical; furthermore, they are commercially available and not radioactive.…”
Section: Introductionmentioning
confidence: 99%